"SAVING DECISIONS IN MENTAL ACCOUNTING: MILLENNIAL GENERATION, GENERATION Z, AND CRYPTOCURRENCY" - Devina Erita Purnomo; Eva Wany Wany (Income, 2025)
This research analyzes the phenomenology that occurs in the digital era in millennials and generation z who work as employees of a company or as entrepreneurs. This approach was chosen because it allows to explore the meaning contained in the life experiences of the research subjects. And this research uses qualitative methods, with primary data sources that use data collection techniques through interviews by measuring several variables, namely: (1) saving decision, (2) mental accounting, (3) millennial generation and generation z, (4) cryptocurrency. The purpose of this study is to understand the decision to save, budget, and invest in cryptocurrency assets of millennials and generation z in several cities in Indonesia. Keywords : Saving Decision, Mental Accounting, Millenial Generation, Cryptocurrency